Indonesia's Struggle Against Cyber ​​Grooming: Reformulating Criminal Law in the Era of Online Prostitution Through Comparative Insights from Malaysia, Singapore, Canada, and Australia - Adinda Maura Salwa; Benny Sumardiana (Program Studi Ilmu Hukum, Fakultas Hukum, Universitas Muslim Indonesia, 2025)
In essence, children can obtain, seek and share information through any media to support their development process. Therefore, the Internet is a platform that children can choose to fulfill their needs. However, the large number of sexual predators roaming social media puts children in a dangerous situation of being exposed to cyber grooming crimes. The methodology chosen in preparing this article is a normative research method that carries out studies by using various related scientific literature. Through this discourse, the fact is obtained that advances in cyber technology have exceeded the regulatory framework in Indonesia, resulting in the slow handling of contemporary forms of crime such as cyber grooming. Therefore, legal policy reform is needed to provide legal certainty in following up on cyber grooming crimes.